A Feminist and Cultural Studies Perspective on Jokha Al Harthi’s Novel Celestial Bodies - SAJJU J, NANDINI; K. BALAKRISHNAN (International Journal of Psychosocial Rehabilitation, 2020)
Though the world bellowed its modernized phase every day, women, the so called weaker sex in all quarters undergo social subjugation in multiple forms in many parts of the world. The condition in the Arab world is a glaring case in point. They are expected to be well bread, dainty and sultry--another flesh of beauty on which men exercise nothing short of exclusive property rights. But the women of the new era have been fighting against all these stereotypes in order to claim their deserved place in society. The Omani author Jokha Al Harthi’s 2019 Man Booker Prize Novel Celestial Bodies (Arab novel Sayyidat al- Qamar, English Trans. Marilyn Booth,) can be seen as one such instance of powerful headways of changes in social perception and the metaphorical conditions of women in that environment. The purpose of this paper is to unveil the contours of the cultural evolution which occurred in the Arab nation of Oman, traditionally quite immune to socio-cultural changes owing to the rigidity of religious and other cultural orthodoxies. Both the domestic/private and public spheres of life are punctuated by a host of conventions, customs and traditions, all weighing heavily on the women folk. Through a cultural analysis of the life experience of the women characters in the novel the paper seeks to explore the nature of the trials and tribulations, the struggles and resistance, and the consequences of such a process towards social liberation.